Effect of malt, wheat and wheat bran extracts on viability of probiotic lactobacilli under acidic conditions - NI Xue-qin; ZENG Dong; PENG Yuan; TANG Yu-rui; ZHENG Xiao-li (浙江大学学报. 农业与生命科学版)
The effect of malt, wheat and wheat bran extracts, glucose and free amino nitrogen (FAN) on the acid tolerance of the potentially probiotic lactobacilli was evaluated under simulating gastric tract conditions. The viability of lactobacilli was investigated during exposure for 3 h at pH 2.5. In the contrast group, the cell population of Lactobacillus johnsonii JJB3, SNZ10 and Lactobacillus reuteri MNZ8, KNZ4 was reduced completely during exposure for 90,30,60 and 30 min, respectively. While, the four strains were protected perfectly in the presence of malt and wheat bran extracts. The survival of L. johnsonii SNZ10 and L. reuteri MNZ8 was very good upon addition of wheat extract, but there was almost no protective effect on L. johnsonii JJB3 and L. reuteri KNZ4. The viability of strains JJB3, SNZ10, KNZ4 was progressively improved as the glucose concentration increased, but addition of yeast extract, used as sources of FAN, did not affect the three strains＇acid tolerance. The results indicate that malt and wheat bran extracts exhibit a significant protective effect on the viability of the four lactobacilli strains under simulating gastric tract conditions, which would be used as good delivery vehicles for probiotic lactobacilli.